African multilingualism viewed from another angle: Challenging the Casamance exception. (August 2021) - Sagna, Serge; Hantgan, Abbie
Aims and Objectives/Purpose/Research Questions: The former region of southern Senegal, the Casamance, has been portrayed throughout the literature on African multilingualism in a singular light, for example, as an area where monolingualism does not exist. The purpose of this article is to stress the previously unacknowledged importance of monolingual settings and practices by discussing data that have yet to be presented in the literature. Design/Methodology/Approach: We investigate rural multilingualism and monolingualism across the Casamance by carrying out the following four studies: (a) we conduct a survey of 62 villages with a questionnaire and our newly created 'blindfold test', classifying them into two main types; (b) with 34 women we study the role of exogamy in multilingual language acquisition in one of the villages; (c) we analyse child language production data and child directed speech to examine the existence of monolingual language acquisition; (d) we examine the sociolinguistic profiles of 101 speakers of one language community to investigate intergenerational multilingualism. Data and Analysis: Data were analysed using descriptive statistics in the form of frequency counts. Additionally, we couch our results on multilingualism in the theory of canonical typology. Findings/Conclusions: We propose a distinction between multilingual settings, e.g. communities where speakers are most likely to accommodate, and who live among villages largely located on national roads and around cities, and monolingual settings, which constitute most of the villages of the Casamance and where language acquisition is monolingual and where migration, rather than exogamy, accounts for the development of individual multilingualism. Originality: This article contributes unprecedented research methodology for the study of complex multilingual situations such as those found in African multilingual contexts. Significance/Implications: Our study adds to the growing understanding of small-scale multilingualism and the emergence of multilingualism in monolingual contexts.